2014
DOI: 10.7554/elife.04353
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of diverse membrane target recognitions by ankyrins

Abstract: Ankyrin adaptors together with their spectrin partners coordinate diverse ion channels and cell adhesion molecules within plasma membrane domains and thereby promote physiological activities including fast signaling in the heart and nervous system. Ankyrins specifically bind to numerous membrane targets through their 24 ankyrin repeats (ANK repeats), although the mechanism for the facile and independent evolution of these interactions has not been resolved. Here we report the structures of ANK repeats in compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
111
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(131 citation statements)
references
References 72 publications
9
111
3
Order By: Relevance
“…Structural and biochemical characterization of the scaffolding molecule ank-G has shown that the ANK repeat domain contains several target binding sites (9). In agreement with this finding, Xu and Cooper reported that the modes of Na V and KCNQ2/3 binding to ank-G differ from each other (10).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Structural and biochemical characterization of the scaffolding molecule ank-G has shown that the ANK repeat domain contains several target binding sites (9). In agreement with this finding, Xu and Cooper reported that the modes of Na V and KCNQ2/3 binding to ank-G differ from each other (10).…”
Section: Discussionmentioning
confidence: 68%
“…Localization of KCNQ2/3 channels of the K V 7 family to the AIS has been proposed to follow the model of VGSCs, because KCNQ2/3 channels contain the same ank-G binding motifs that trap VGSCs (8). Moreover, VGSCs and KCNQ2/3 channels both bind to the ankyrin repeats in ank-G, albeit at distinct but overlapping interaction sites (9,10). However, other determinants for AIS localization outside of the ankyrin-binding motif have been described, thus pointing to additional modes of regulation (11)(12)(13).…”
mentioning
confidence: 99%
“…Repeats 5 and 6 are coded on the same exon (exon 6 in vertebrates; Fig. 5E) and are the only repeats that break the canonical 33 residue per repeat pattern (39) and structure (14,40); see "Discussion"). Deletion of exon 6/R5-6 resulted in an N-R4 fragment that showed markedly reduced binding to either anchor (Fig.…”
Section: Ck2 Inhibitor Treatment Decreases Co-localization Of Mb-gfp mentioning
confidence: 99%
“…Each 33-residue ankyrin repeat consists of a right-handed solenoid: half ␤-hairpin, two short antiparallel ␣-helices, a "loop" directed back toward the hairpin, and a second half ␤-hairpin. This pattern is followed in AnkG R1-7, except for R5-R6, which preserves the solenoidal periodicity but replaces the hairpin with a longer R6 front helix and longer loop (40). Locations of hairpin tips residues H1, H2, H4, H5, and H7 are labeled green; H3 tip KK implicated in Na v binding is labeled red.…”
Section: A Ankg Mb Domainmentioning
confidence: 99%
See 1 more Smart Citation